1996
DOI: 10.1002/(sici)1096-9918(19960930)24:10<718::aid-sia182>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Polyethylene Terephthalate with Excimer UV Radiation

Abstract: Buformin is a widely used as an antidiabetic agent but its renal excretion is still controversial. A new HPLC method with ultraviolet (UV) detection for the determination of buformin in plasma and urine has been developed. After protein precipitation or dilution, buformin and internal standard phenformin were resolved on an octadecyl silica column and detected by UV detection at 233 nm. Intra‐ and inter‐day coefficients of variation were <9%. The limit of quantification was around 0.05 µg/ml for plasma and 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…Therefore, it can be inferred that the etching process with incoherent UV radiation of excimer lamps is mainly of a photolytic nature. Similar results have been reported by Zhang, Boyd, and Esrom (1996), with a 222 nm excimer lamp.…”
Section: Sem Analysissupporting
confidence: 91%
“…Therefore, it can be inferred that the etching process with incoherent UV radiation of excimer lamps is mainly of a photolytic nature. Similar results have been reported by Zhang, Boyd, and Esrom (1996), with a 222 nm excimer lamp.…”
Section: Sem Analysissupporting
confidence: 91%
“…The trend is partially caused by both the polydispersed PAA chain length and the agglomeration of the grafted chains to irregular islands on the PET surfaces during the drying process. Moreover, it has been recently shown that the surface roughness of PET surface during UV irradiation is positively correlated with both UV intensity and exposure time [16]. The extensive roughening of PET surfaces at the microscale (on a larger field of view of 15 Â 15 mm) as a result of PAA grafting is further confirmed by scanning electron microscopy (data not shown).…”
Section: Results and Disucssionmentioning
confidence: 65%
“…Therefore, the modification and control of the surface properties of PET is a research topic for materials processing in the last decades. The oxidation and the etching of the PET surface have been attempt by the dry processes such as UV radiation [1][2][3][4][5][6] and plasma exposure [7][8][9][10], which produce no toxic or hazardous liquids from the treatment processes.…”
Section: Introductionmentioning
confidence: 99%